Endodontic Treatment of Complex Dens Invaginatus Teeth with Long Term Follow-Up Periods - de Oliveira, NatÃ¡lia Gomes; da Silveira, Marina TorreÃ£o; Batista, Shirley Machado; Veloso, Sirley Raiane Mamede; Carvalho, Marianne de Vasconcelos; Travassos, Rosana Maria Coelho (Iranian Endodontic Journal, 2018)
Dens invaginatus is characterized by invagination of enamel and dentin in the dental papilla prior to tissue calcification. This malformation commonly occurs in the maxillary lateral incisors. The present study reports two complex endodontic treatments in Oehlers’ type II and III dens invaginatus, with periapical lesion and presence of bone resorption. In the reported cases, conventional endodontic therapy was successful and sufficient enough to eliminate the infectious process, allowing periapical bone neoformation and absence of symptomatology. Dens invaginatus is a relatively easy-to-diagnose dental malformation. However, it is necessary to know its radiographic aspects. The treatment results demonstrated that, although the cases of dens invaginatus of high complexity are challenging, an accurate diagnosis accompanied with proper endodontic treatment can avoid unnecessary surgical intervention and allow great chances of favorable prognosis in long term. Keywords: Anomalies; Classification; Dens Invaginatus; Root Canal Therapy